PENGARUH PROFITABILITAS, LEVERAGE DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Saputra, Moses Dicky Refa; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis researchis aimed to examine the influence of profitability, leverage, and corporate governance on taxavoidance in Kompas 100 Index companies which arelisted in Indonesia Stock Exchange in the period ofFebruary 2013-January 2016.The independent variables in this research is the Return on Assets (ROA), Debt toEquity Ratio (DER), the audit committee and independent commissioner.Meanwhile, the dependent variable inthis researchis Cash Effective Tax Rate (CETR). This research uses 44 samples which have been obtained fromKompas 100 index companies which arelisted on the Indonesia Stock Exchange in the period of February 2013-January 2016, during 3 years of observation,132 annual reports have been analyzed.The sample collectiontechnique has been done by usingpurposive sampling and the data analysis tools has been done byusing multiplelinear regression analysis. The result of the research indicates that the DER has positive and significantinfluenceto the tax avoidance with its coefficient regression is 0.011 and its significant level is 0.026,independent commissioner has significant and negative influenceto the tax avoidance with its coefficientregression is -0.388 and its significance level of 0.000.As for the DER and the audit committee does not have anysignificant influenceto the tax avoidance.Keywords: profitability, leverage, audit committee, independent commissioners, tax avoidance